2020
DOI: 10.1002/ppsc.202000001
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape Effects of Near‐Infrared Light‐Activatable Cu2(OH)PO4 Nanostructures on Phototherapeutic Destruction of Drug‐Resistant Hypoxia Tumors

Abstract: Development of simple, robust, and noninvasive therapeutic approaches to treat cancers and improve survival rates is a grand challenge in clinical biomedicine. In particular, the sizes and shape of the nanomaterials play a vital role in dictating their biodistribution and clearance pathways. It remains elusive how the size and shape of a nanomaterial affect its therapeutic efficacy in cancer diagnosis and treatments. To tackle the above problem, the effects of size and shape of Cu2(OH)PO4 nanostructures (nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The 13 C NMR peak at 175 ppm indicates the formation of a −COOH functional group. 31 The plasmonic CuO/Cu 2 O TNCs did not show any noticeable changes in their morphology and optical characteristics after conjugation with the F127-COOH polymer (Figure S3(A) and (B)). Further, anti-EGFR moieties were chemically attached onto F127-COOH-coated plasmonic CuO/Cu 2 O TNCs via a 1ethyl-3-(3-(dimethylamino)propyl) carbodiimide (EDC)mediated coupling process.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The 13 C NMR peak at 175 ppm indicates the formation of a −COOH functional group. 31 The plasmonic CuO/Cu 2 O TNCs did not show any noticeable changes in their morphology and optical characteristics after conjugation with the F127-COOH polymer (Figure S3(A) and (B)). Further, anti-EGFR moieties were chemically attached onto F127-COOH-coated plasmonic CuO/Cu 2 O TNCs via a 1ethyl-3-(3-(dimethylamino)propyl) carbodiimide (EDC)mediated coupling process.…”
Section: Resultsmentioning
confidence: 98%
“…The F127-COOH polymer was synthesized using the literature procedure, and the chemical structure was confirmed using 13 C NMR analysis (see Figure S2). The 13 C NMR peak at 175 ppm indicates the formation of a −COOH functional group . The plasmonic CuO/Cu 2 O TNCs did not show any noticeable changes in their morphology and optical characteristics after conjugation with the F127-COOH polymer (Figure S3­(A) and (B)).…”
Section: Resultsmentioning
confidence: 99%
“…[238] Hwang et al proposed a different strategy to treat drug-resistant hypoxic tumors. [273] They developed two types of Cu 2 (OH)PO 4 nanosystems: nanosheets and QDs, and compared the effect of their size and shape on destroying malignant and hypoxic drug-resistant lung tumors via PDT. The Cu 2 (OH)PO 4 nanosheets could produce OH radicals to eliminate cancer cells upon NIR light irradiation under an O 2 deprivation condition, thereby overcoming drug resistance in the hypoxic TME.…”
Section: Addressing Chemoresistancementioning
confidence: 99%
“…[34] Hwang and co-workers prepared larger-sized Cu 2 (OH)PO 4 nanosheets and smaller-sized Cu 2 (OH)PO 4 quantum dots for tumor PDT, and systematically studied how the size and shape of nanomaterials affected their therapeutic effect in the treatment of drug-resistant lung tumors. [35] It was found that compared with small-sized spherical quantum dots, nanosheets with larger sizes have significant advantages in tumor passive targeting and ROS generation, providing a basis for optimizing the physicochemical properties of nanomaterials to improve PDT.…”
Section: Tumor Targeted Delivery Of Pamentioning
confidence: 99%